Evaluation of toxicity of Acacia angustissima in a rat bioassay - Smith, A.H.; Odenyo, A.A.; Osuji, P.O.; Wallig, M.A.; Kandil, F.E.; Seigler, D.S.; Mackie, R.I. (Elsevier, 2001)
Acacia angustissima has potential as a fodder tree, but was toxic to sheep when fed without adaptation at levels higher than 50 g per day in previous studies. In the present study it was determined that rats are sensitive to anti-nutritional factor(s) of A. angustissima and can therefore be used in bioassays to evaluate the toxicity of this legume. Weanling rats fed a diet supplemented with 7.5% A. angustissima had reduced intake and average daily gain (ADG) (4.5 and -0.8 g/d) when compared to rats fed a diet containing 7.5% Medicago sativa (6.8 and 2.4 g/d). When A. angustissima leaves were incubated in the rumen of steers for 24 h before feeding to the rats no toxicity symptoms were observed suggesting that the anti-nutritional factors were either transformed by rumen microbial activity, solubilized out of the plant leaves or reduced due to oven drying. Variable mild lymphocytic typhlitis was observed in cecal tissues in both groups fed 7.5% A. angustissima, either whole or after rumen incubation. No other significant histological or gross pathological changes were observed. In order to ascertain the nature of the anti nutritional factor(s) milled A. angustissima leaf material was extracted with a variety of solvents and extracts added to rat diets to determine their effect. Intake and ADG (6.0 and 0.5 g/d) were significantly reduced in rats fed a diet containing a 70% acetone extract compared to the rats fed the control diet (8.8 and 3.1 g/d). The rats fed the 70% acetone extract containing diet showed an increase in cecal wet weight and/or contents, salivary gland dry weight (% of live weight), fecal nitrogen excretion and increased concentrations of proline, glycine and glutamic acid in the feces. Further fractionation of a 70% acetone fraction was performed to yield ethyl acetate, acetone and watersoluble fractions. Again intake and ADG (6.7 and 0.2 g/d) were significantly reduced in rats fed a diet containing a 70% acetone extract compared to the rats fed the control diet (10.7 and 3.6 g/d). In vitro incubation of the 70% acetone fraction with rumen fluid did not result in significant microbial transformation of the anti-nutritional factors (7.4 and 0.1 g/d). Intake and ADG were significantly reduced when compared to the control diet in the diet containing the ethyl acetate soluble fraction (8.6 and 2.1 g/d), but no anti-nutritional effects were noted in the diets containing the acetone (11.3 and 3.8 g/d) or water-soluble fractions (11.1 and 3.8 g/d) of the 70% acetone extraction. The size increase in salivary glands, increased fecal nitrogen excretion and increased concentrations of proline, glycine and glutamic acid in the feces together with decreased intake and ADG when diets are fed containing phenolics indicate that phenolics were the major component involved in the antinutritional effects of A. angustissima used in these studies. Condensed tannins, but not gallotannins, were detected in phenolic-containing plant extracts. Inhibition of intake and weight gain of condensed tannin containing diets was reversed by polyethylene glycol, which complexes with tannins.